Rodrigo García: From Honey to Ash - Checa Puerta, Julio (2018)
Nearly all of the works written between 1986 and 2009 by the playwright Rodrigo García are included in the volume titled Cenizas escogidas (2009) and in a large part of his theater the food appears as a central element, both at the textual level on the scenic or performative plane. It is evident that few themes can find in the history of art greater richness of expressive possibilities than food, and the connection that Lévi Strauss understood so well between food and culture is a constant that Rodrigo García explores artistically in order to offer a penetrating reflection on contemporary society and on the individuals who conform it. Rodrigo García’s play (1964) may be identified with the trend that Hans Thies Lehmann has called Posthramatic Theater (Lehmann, 1999). Within this heterogeneous label we find many of the most outstanding representatives of the stage renovation of the last third of the 20th century, from Tadeusz Kantor to Robert Wilson, to Heiner Müller, Peter Brook, Pina Bausch, Jan Fabre and Elfriede Jelinek, among others.